Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00586-010-1418-6
|View full text |Cite
|
Sign up to set email alerts
|

Pedicle versus laminar screws: what provides more suitable C2 fixation in congenital C2–3 fusion patients?

Abstract: Patients with Klippel-Feil syndrome (KFS) have congenital fusions of at least 1 cervical motion segment, and often present with compensatory hypermobility or symptomatic stenosis of the cranio-vertebral junction which requires occipitocervical reconstruction and fusion. One subgroup of KFS patients in which this is particularly common is those with isolated C2-3 congenital fusion (C2-3 CF). The anatomic suitability for C2 pedicle and laminar screw placement had been analyzed in the general adult population, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
(34 reference statements)
0
23
0
3
Order By: Relevance
“…Various congenital osseous anomalies at the craniocervical junction have been reported [11][12][13][14][15][16][17][18][19][20][21]. In the current study, the congenital lesions include os odontoideum, occipitalization of the atlas, congenital C2-3 fusion, congenital atlantoaxial subluxation, congenital basilar invagination and combined anomalies.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Various congenital osseous anomalies at the craniocervical junction have been reported [11][12][13][14][15][16][17][18][19][20][21]. In the current study, the congenital lesions include os odontoideum, occipitalization of the atlas, congenital C2-3 fusion, congenital atlantoaxial subluxation, congenital basilar invagination and combined anomalies.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, occipitalization of the atlas was associated with congenital C2-3 fusion in three patients and os odontoideum in one. Occipitalization of the atlas, in association with congenital C2-3 fusion, exerts more strain on the atlantoaxial articulation during flexion and extension [15,16]. Repeated excessive strain at this joint more likely predisposes a patient to atlantoaxial instability.…”
Section: Discussionmentioning
confidence: 99%
“…Fin [10] reported several drawbacks of the C2 laminar screw including associated reduced the surface of fusion bed and biomechanically weaker than the C2 pedicle screws. It was also indicated by Wang et al [34] that the C2 laminar screw had less force when act as a posterior anchor in comparison with the pedicle screw. In the present study, 20 C2 pedicles from 14 patients were found to have a diameter less than 5.5 mm.…”
Section: Discussionmentioning
confidence: 87%
“…For an average adult, the mean diameter and length of C2 pedicle are 5.8-8 and 24-31 mm, respectively [25,27,34,37], and those of C2 lamina are 5.75-6.3 and 24.6-31.6 mm [4,7,32]. These parameters should allow the use of both pedicle and laminar screws for C2 fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation